Incised Glass Vessels from the Umayyad and Abbasid-Fatimid Periods at Bet Shean, Israel - Hadad, Shulamit (Bulletin of ASOR, 2000)
Twenty-two vessels-incised glass beakers, bowls, and one bottle-made of dark blue, yellowish green, yellowish brown, olive, and dark purple glass and dated to the Umayyad and Abbasid-Fatimid periods were discovered at Bet Shean in the excavations conducted by the Hebrew University of Jerusalem expedition, headed by Gideon Foerster and Yoram Tsafrir, in 1980-1981 and 1986-1997. Two sherds are from the Umayyad period, and twenty vessels or fragments are dated to the Abbasid-Fatimid periods. Twenty vessels will be presented in this article, while the other two are very small fragments. The beakers and bowls are deep and have straight or rounded walls. The bottle, complete except for its neck, is very similar in its geometric designs to the other vessels, and apparently all the vessels from Bet Shean were made in one workshop.